Triste sina ser poeta de latrina: um estudo antropológico/artístico dos grafitos de banheiro - Santos, Ludmila Helena Rodrigues dos (2012)
This paper conducted a study of graffiti from public toilets in the city of São Paulo. The focus of analysis is the ability agentive these demonstrations, and to access these intentions and meanings, we sought a dialogue between anthropology and artistic methodologies, experimenting and meanings through interactions of bathrooms installations and interventions, exploring and evoking sensory looks like, smells and communications. To underscore the graffiti, highlight the typical sense of the bathroom and bring to this environment other artistic textures, in addition to their senses of anonymity, transgressor in that uses an area of conservation and public use, subjective and individualized, brings a problematization and theoretical tract of these productions and locations beyond possible interpretations of content and classificatory generalizations. We seek to understand how intentions abandoned in places highly significant gain autonomy for interaction and enable the understanding of a theory of action grounded in production and not in human producers.